Implementation of Pulmonary TB Case Finding in the Preventation of Tuberculosis at the Tanah Tinggi Public Health Center - Syaharani Adzra; Susilawati Susilawati (EKSAKTA: Berkala Ilmiah Bidang MIPA, 2023)
The success of TB management in Indonesia is determined through 3 indicators, namely Case Notification Rate (CNR), Case Detection Rate (CDR), and Succes Rate. In 2022  Tanah Tinggi Public Health Center experienced a decrease in case discovery with a figure of 393 cases, this figure is lower than in 2020, namely 522 cases. The purpose of this study is to determine implementation case discovery in an effort to overcome TB at the Tanah Tinggi Health Center. This research was conducted in October 2022 using a qualitative method, primary data collection was obtained through in-depth interviews of Public Health Center officers and TB patients. The research informants were 7 people with 3 main informants and 4 triangulation informants. The results of the study found that policy followed PERMENKES No. 67 of 2016. Communication with the community is still constrained by the bad stigma that spreads. Implementing personnel at the Puskesmas are not sufficient in quantity and quality, and there is duplicate work that causes obstacles to achievement targets, scheduling activities have not been determined and case findings are also still passive. The implementation of TB case discovery at puskesmas has not reached the target because case discovery has decreased since 2020.